Auto Arginine-GlcNAcylation Is Crucial for Bacterial Pathogens in Regulating Host Cell Death - Xue, Juan; Pan, Xing; Peng, Ting; Duan, Meimei; Du, Lijie; Zhuang, Xiaohui; Cai, Xiaobin; Yi, Xueying; Fu, Yang; Li, Shan (Frontiers in Cellular and Infection Microbiology, 2020)
Many Gram-negative bacterial pathogens utilize the type III secretion system (T3SS) to inject virulence factors, named effectors, into host cells. These T3SS effectors manipulate host cellular signaling pathways to facilitate bacterial pathogenesis. Death receptor signaling plays an important role in eukaryotic cell death pathways. NleB from enteropathogenic Escherichia coli (EPEC) and SseK1/3 from Salmonella enterica serovar Typhimurium (S. Typhimurium) are T3SS effectors. They are defined as a family of arginine GlcNAc transferase to modify a conserved arginine residue in the death domain (DD) of the death receptor TNFR and their corresponding adaptors to hijack death receptor signaling. Here we identified that these enzymes, NleB, SseK1, and SseK3 could catalyze auto-GlcNAcylation. Residues, including Arg13/53/159/293 in NleB, Arg30/158/339 in SseK1, and Arg153/184/305/335 in SseK3 were identified as the auto-GlcNAcylation sites by mass spectrometry. Mutation of the auto-modification sites of NleB, SseK1, and SseK3 abolished or attenuated the capability of enzyme activity toward their death domain targets during infection. Loss of this ability led to the increased susceptibility of the cells to TNF- or TRAIL-induced cell death during bacterial infection. Overall, our study reveals that the auto-GlcNAcylation of NleB, SseK1, and SseK3 is crucial for their biological activity during infection.